Quản lí hoạt động tự đánh giá trong kiểm định chất lượng giáo dục tại một số trường trung học phổ thông công lập quận Gò Vấp, Thành phố Hồ Chí Minh - Đỗ , Đình Thái; Nguyễn , Quốc An (Tạp chí Giáo dục, 2024)
Education quality is always an issue of concern to society because of its importance to the country's development in general and education in particular. To ensure and improve education quality, education quality accreditation is used as an effective tool; schools need to conduct self-assessment activities as well as implement operational management plans. This action is because this is the first step and plays an important role in building the foundation for the next steps in the educational quality accreditation process. The article addresses related concepts, the importance of managing self-assessment activities and analyzes the current situation of self-assessment management in education quality accreditation at district public high schools. Go Vap, Ho Chi Minh City today. The research results will be the basis for proposing measures to improve the effectiveness of self-assessment management in education quality accreditation in schools.